Understanding audiences : learning to use the media constructively - Wicks, Robert H. (LEA's communication series., 2000)
This text examines how audiences develop their perceptions of reality based on what they see in the media. It is appropriate for students in media effects, psychology of media, media and society, and audience analysis.